Penyuluhan Pertanian dan Kesetaraan Gender dalam Usahatani Jagung Pertanian Lahan Kering di Kecamatan Jerowaru Lombok Timur - Hayati, Hayati; Sahidu, Arifuddin; Muktasam, Muktasam; Karyadi, Lalu Wiresapta; Suadnya, Wayan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Rural women participate in implementing food crop farming activities both in paddy fields and dry land. This participation should be followed by women's participation in agricultural extension activities and the realization of gender equality in farming. This research is aimed at analyzing the level of gender equality in corn farming in dry land farming and the agricultural extension factors that influence it. The research location is in Jerowaru District with the sample villages being Seriwe Village (hill land) and Sekaroh Village (moor land). Data was collected using survey techniques by conducting interviews with 60 respondents. Data were analyzed descriptively using scoring, Mann-Whitney difference test and Rank Spearman correlation analysis test. The research results found that the level of gender equality in corn farming is relatively high and is influenced by agricultural extension support factors. Thus, strengthening the implementation of gender responsive extension needs to be improved to realize equality in access and control of resources, women's participation in corn farming and obtaining benefits.